Analisis Optimalisasi Sistem Penagihan Piutang Negara di DJKN Jawa Tengah dan D.I. Yogyakarta - Sukmawati, Ayu; Ira Setiawati (Jurnal Ilmiah Aset, 2025)
The collection of state receivables is a crucial element in the management of state finance as it plays a direct role in optimizing state revenue and improving budget efficiency. This study aims to analyze the collection system of state receivables implemented by the Directorate General of State Assets (DJKN) Regional Office of Central Java and D.I. Yogyakarta, as well as to identify the obstacles and optimization efforts made in its implementation. The method used is qualitative descriptive with data collection techniques through interviews, observations, and document studies. The results show that the process of collecting state receivables has followed the provisions of the Minister of Finance Regulation Number 240/PMK.06/2016, starting from document verification to the execution of seizures and write-offs of receivables. In its implementation, it still faces various obstacles such as incomplete documents, low debtor compliance, difficulties in asset execution, and limited human resources. DJKN has implemented various optimization strategies such as persuasive approaches, handling problematic receivables, direct field collection, strengthening cross-agency synergy, utilizing information technology, and submitting requests for the write-off of uncollectible receivables. These efforts are expected to enhance the effectiveness of collection and strengthen the governance of state finances.